Silicas with Polyoxyethylene Branches for Modification of Membranes Based on Microporous Block Copolymers - Ilsiya M. Davletbaeva; Zulfiya Z. Faizulina; Ekaterina D. Li; Oleg O. Sazonov; Sergey V. Efimov; Vladimir V. Klochkov; Alexander V. Arkhipov; Ruslan S. Davletbaev (Membranes, 2023)
We have synthesized cubic and linear polysiloxanes containing polyoxyethylene branches (ASiP-Cu) using tetraethoxysilane, polyoxyethylene glycol, and copper chloride as precursors; the products are stable to self-condensation. The effect of copper chloride content on the chemical structure of ASiP-Cu has been established. A special study was aimed at defining the modifying effect of ASiP-Cu on the sorption characteristics of membranes based on microporous, optically transparent block copolymers (OBCs). These OBCs were produced using 2,4-toluene diisocyanate and block copolymers of ethylene and propylene oxides. The study demonstrated significantly increased sorption capacity of the modified polymers. On the basis of the modified microporous block copolymers and 1-(2-pyridylazo)-2-naphthol (PAN) analytical reagent, an analytical test system has been developed. Additionally, the modified OBCs have the benefit of high diffusion permeability for molecules of organic dyes and metal ions. It has been shown that the volume of voids and structural features of their internal cavities contribute to the complex formation reaction involving PAN and copper chloride.